2019
DOI: 10.29252/wjps.8.1.25
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Care Compact Disk-Based Instruction Program on Physical Performance and Quality of Life of Patients with Burn At-Dismissal

Abstract: BACKGROUNDBurn injuries still negatively influence the various aspects of life like physical performance and quality of life. This study was conducted to investigate at-dismissal self-care compact disk-based instruction program on the physical performance life quality of the patients with burns. METHODS One-hundred burn patients in Shahid Motahhari Burn Center, Tehran, Iran were randomly assigned to two equal groups of intervention (n=50) and control (n=50). The latter received only routine dismissal self-care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Rezaei et al 23 showed that both telenursing and face‐to‐face training can be used to improve the QoL of survivors of burn injuries during rehabilitation. Another prospective study found that at‐dismissal self‐care compact disk‐based instruction program can increase physical performance and QoL of patients with burns 24 . The results of this study showed that after the intervention, the mental health, emotional functioning, social functioning, vitality status, physical pain, physical functioning, physical functioning, and general health of the SBC group were all higher than those of the control group ( P < 0.05, respectively), suggesting that SBC‐based nursing intervention could effectively improve the QoL of diabetic patients with scalds.…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei et al 23 showed that both telenursing and face‐to‐face training can be used to improve the QoL of survivors of burn injuries during rehabilitation. Another prospective study found that at‐dismissal self‐care compact disk‐based instruction program can increase physical performance and QoL of patients with burns 24 . The results of this study showed that after the intervention, the mental health, emotional functioning, social functioning, vitality status, physical pain, physical functioning, physical functioning, and general health of the SBC group were all higher than those of the control group ( P < 0.05, respectively), suggesting that SBC‐based nursing intervention could effectively improve the QoL of diabetic patients with scalds.…”
Section: Discussionmentioning
confidence: 99%
“…Hand motor function was assessed using an observational checklist developed by the researchers after a careful review of the related studies (e.g., Ardebili et al, 2014;Lotfi et al, 2020). It was comprised of three crucial hand activities: the ability to rotate the wrist, bend the wrist, and bend the fingers.…”
Section: Hand Motor Function Observational Checklistmentioning
confidence: 99%
“…Burns are injuries caused by the application of chemicals, heat, radiation, or electrical current to the body's inner or outer surface, resulting in tissue depletion (Tiwari, 2012). Burn injuries are a significant public health concern worldwide and the fourth most common injury, which can result in high mortality and morbidity (Mamashli et al, 2019). Burns are also the leading cause of disability-adjusted life-years in underdeveloped countries, accounting for 96% of all fire-related deaths (Forbinake et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach which would complement this is to increase provider confidence in patient adherence by systematically supporting patient self-management. In the UK a number of recognised self-management strategies have been independently adopted by patients with chronic burns [60] and though there are limited examples even modest self-management support has seen improved adherence in those with more serious burns [61,62].…”
Section: Meeting the Challenge Of Implicit Bias In Burn Carementioning
confidence: 99%